Measuring the diaspora for virus-specific CD8(+) T cells - Marshall, Dana R. (The National Academy of Sciences, 2001)
The CD8(+) T cell diaspora has been analyzed after secondary challenge with an influenza A virus that replicates only in the respiratory tract. Numbers of D(b)NP(366)- and D(b)PA(224)-specific CD8(+) T cells were measured by tetramer staining at the end of the recall response, then followed sequentially in the lung, lymph nodes, spleen, blood, and other organs. The extent of clonal expansion did not reflect the sizes of the preexisting memory T cell pools. Although the high-frequency CD8(+) tetramer(+) populations in the pneumonic lung and mediastinal lymph nodes fell rapidly from peak values, the “whole mouse” virus-specific CD8(+) T cell counts decreased only 2-fold over the 4 weeks after infection, then subsided at a fairly steady rate to reach a plateau at about 2 months. The largest numbers were found throughout in the spleen, then the bone marrow. The CD8(+)D(b)NP(366)(+) and CD8(+)D(b)PA(224)(+) sets remained significantly enlarged for at least 4 months, declining at equivalent rates while retaining the nucleoprotein > acid polymerase immunodominance hierarchy characteristic of the earlier antigen-driven phase. Lowest levels of the CD69 “activation marker” were detected consistently on virus-specific CD8(+) T cells in the blood, then the spleen. Those in the bone marrow and liver were intermediate, and CD69(hi) T cells were very prominent in the regional lymph nodes and the nasal-associated lymphoid tissue. Any population of “resting” CD8(+) memory T cells is thus phenotypically heterogeneous, widely dispersed, and subject to broad homeostatic and local environmental effects irrespective of epitope specificity or magnitude.